Fuzzy logic-based MPPT control for solar PV fed three-phase induction motor drive in water pumping applications - K. Chitanya; Arjyadhara Pradhan; Babita Panda (Institute of Advanced Engineering and Science, 2026)
The reliance on traditional energy sources for the agricultural water pumping framework leads to higher operational costs and environmental concerns. The partial shadings severely reduce the solar photovoltaic based water pumping framework efficacy. Owing to partial shading conditions, the output power of the photovoltaic array degrades, which reduces the water pumping output. Therefore, this article presents a low-cost solar photovoltaic fed three phase induction motor driven system, which helps for the rural water pump application. Here, maximum power point tracking of solar photovoltaic panel is done by fuzzy logic. Usually, the solar panel gives direct current power is stored in recharging battery and then setups and acts as source for voltage source inverter in the standalone model. A novel single step battery-low power transformation is used by developing a fuzzy maximum power track with buck-boost chopper that makes the total setup cost to reduced significantly. Mamdani fuzzy system is selected for maximum power point tracking (MPPT) controller because it has more intuitive and easier to understand If-Then rule bases. The suggested method is worked as a model having photovoltaic array, maximum power tracking with the buck-boost chopper, voltage source inverter, and three phase induction motor drive. The inverter is used sinusoidal pulse width modulation as the control algorithm. To check the simulation results the total set up is carried out in MATLAB software. The test results observed that the proposed prototype is useful. It’s efficacy i.e., 75% with in response time (1 sec) for different insulations and temperatures.